Administrators’ roles in training programs and training transfer = Peran administrasi pada program pelatihan dan transfer pelatihan - Ismail, Azman; Ng, Kueh Hua; Ismail, Yusof; Abu Samah, Ainon Jauhariah; Abu Bakar, Rizal; Ibrahim, Nurshahira (Faculty of Economics, Universitas Negeri Semarang, Indonesia, 2015)
An administrator plays a vital role in the growth and development of his/her subordinates. Despite this notion, the role of an administrator in the context of training programs and transfer of training is not well studied. Therefore, this study is set to examine the relationship between administrator’s role in training programs and training transfer. A survey method was utilized to gather 706 survey questionnaires from employees of local authorities of three cities in the state of Sarawak, Malaysia. The results of SmartPLS path model analysis confirmed that the ability of administrators to properly implement support, communication and assignment in planning and implementing training programs has been an important predictor of training transfer in the studied organization. Further, this study provides discussion, implications and conclusion.